ANALYSIS OF FACTORS EFFECTING PROFIT GROWTH WITH FIRM SIZE AS MODERATING VARIABLE - Caprisa, Dhea Sarah; Telaumbanua, Dian Hardiknatasya; Barus, Andreani Caroline; Firza, Syafira Ulya (Fakultas Bisnis Universitas Mikroskil, 2024)
This study aims to determine and analyze the influence of liquidity, profitability, leverage, activity, and inventory turnover on profit growth with the firm size of the company as a moderation variable at Consumer Non-Cyclical Companies Listed in the Indonesia Stock Exchange period 2017-2021. The sampling method used is purposive sampling and obtained samples of 65 companies with a number of observations of as much as 325 from the Consumer Non-Cyclical Company Listed in the Indonesia Stock Exchange period 2017-2021. The data analysis method used was Partial Least Square - Structure Equation Modeling with a two-stage approach model using the SmartPLS 3.2.9. The test results show that liquidity, profitability, leverage, activity, and turnover of inventories have no effect on profit growth at the Consumer Non-Cyclical Company Listed. The result of moderation testing shows that the firm size of the company is only able to moderate (weaken) activity relationship with profit growth, while the firm size is unable to moderate liquidity, profitability, leverage, and inventory turnoverÂ at Consumer Non-Cyclical Company Listed.